Probabilistic Estimation of Bromate Exposure from the Consumption of Bottled Drinking Water Distributed in the Bogor Region - Yani Handayani; Puspo Edi Giriwono; Dian Herawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Bottled drinking water is a source of human exposure to bromate, a disinfection by-product (DBP) with adverse health effects and carcinogenic potential. Little is known about bromate exposure levels and risk characterization, particularly in Bogor, Indonesia. The study aimed to obtain data on bromate concentrations in bottled drinking water, estimate bromate exposure levels based on individual consumption, and assess the risk characterization. Bromate exposure were calculated based on bromate concentrations and individual consumption, across five age groups. Bromate exposure and risk characterization were estimated probabilistically using Monte Carlo simulation. In this study, 37 bottled drinking water samples were collected from large and small manufacturers and retailers in Bogor and analyzed for bromate content. Bromate was detected in 30 samples, with 5 samples exceeding the Indonesian national standard of 10 µg/L. The average concentration was 6.88±8.88 μg/L. Exposure estimates indicate that, for all age groups, the average and 95th percentile values are 0.1086±0.0484 µg/kg BW/day and 0.4044 µg/kg BW/day in Bogor and 0.1492±0.2820 µg/kg BW/day and 0.5495 µg/kg BW/day in Indonesia, respectively. Values below the tolerable daily intake (TDI) limit for non-cancer risk, so the risk characterization for all age groups can be considered as safe.